Synthesis, crystal structure, and luminescence properties of a three-dimensional coordination polymer from europium(iii) carbonate hemioxalate hydrate. Issue 44 (26th October 2022) - Takano, Rina; Ishida, Takayuki; Ay, Burak
Abstract : A new luminescent lanthanide coordination polymer composed of europium(iii ), oxalate and carbonate was prepared. Abstract : A new luminescent lanthanide coordination polymer composed of europium(iii ), oxalate and carbonate was prepared. A hydrothermal synthesis technique was applied to an aqueous solution of europium(iii ) nitrate and oxalic acid (H2 ox), resulting in a carbonate-fixed compound, [Eu2 (ox)(CO3 )2 (H2 O)2 ] n, which was characterized using elemental, spectroscopic, thermal and crystallographic analyses. The number of aqua ligands could be reduced in comparison with the known europium(iii ) oxalate pentahydrate. The present reaction can be regarded as a rare example, where CO2 was incorporated into a compound under acidic reaction conditions. An infinite layer comprises Eu 3+ and carbonate ions parallel to the crystallographic ac plane, and ox anions bridge the layers as a pillar in the b direction, thus affording a three-dimensional polymer in an orthorhombic crystal system. The photophysical properties were studied based on the emission spectra. The emission quantum yield was found to be 10.6% (excited at 400 nm), despite the presence of water as a ligand. Antenna effects do not work in the present compound. The lifetimes were 0.40, 0.41, and 0.37 ms for the emissions at 590, 615, and 690 nm, respectively, which are longer than that of the known europium(iii ) oxalate pentahydrate.